2018
DOI: 10.15809/irriga.2016v21n2p395-408
|View full text |Cite
|
Sign up to set email alerts
|

Estudo Comparativo Da Evapotranspiração De Referência Entre Localidades No Estado De São Paulo E Na Província De Habana

Abstract: ESTUDO COMPARATIVO DA EVAPOTRANSPIRAÇÃO DE REFERÊNCIA ENTRE LOCALIDADES NO ESTADO DE SÃO PAULO E NA PROVÍNCIA DE HABANA FRANCISCA FRANCIANA SOUSA PEREIRA1; ENZO DAL PAI2; RANSES J. VÁZQUEZ MONTENEGRO3; RODRIGO MÁXIMO SÁNCHEZ ROMÁN4; ALBA MARÍA GUADALUPE ORELLANA GONZÁLEZ5 E JOÃO FRANCISCO ESCOBEDO6 1Professora Depto. de Engenharia Rural - UNESP/FCA, C.P. 237; CEP: 18610-307 –  Botucatu, SP – Brasil. E-mail autor principal: francanasousap@gmail.com2Professor Depto. de Engenharia Rural - UNESP/FCA, Botucatu, SP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
1
1
0
1
Order By: Relevance
“…April, May and June were the months with the lowest values (2.7 m s -1 ). This result confirms the study of Pereira et al (2016), who found that June showed the lowest value for maximum wind speed when evaluating the mean monthly data of climatic variables.…”
Section: Resultssupporting
confidence: 91%
“…April, May and June were the months with the lowest values (2.7 m s -1 ). This result confirms the study of Pereira et al (2016), who found that June showed the lowest value for maximum wind speed when evaluating the mean monthly data of climatic variables.…”
Section: Resultssupporting
confidence: 91%
“…According to Köppen's classification, the local climate is a Cwa type, which stands for subtropical or tropical of altitude (Pereira et al, 2016). The lowest temperatures were registered during the second experimental quarter, with a thermal sum of 1694ºC ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Essa correlação espacial com altitude foi verificada em Cuba por Solano et al (2003); os autores verificaram, por meio de mapas de ETo, que os gradientes de variação da ETo apresentam valores cada vez menores com o aumento da altitude. Essa mesma tendência foi observada em Botucatu e Piracicaba, no Brasil e Güira de Melena, em Cuba (PEREIRA et al, 2016). 1 27,0 14,8 46,1 10,6 79,4 12,1 110,1 11,5 2 28,3 16,1 49,9 13,5 89,4 11,8 127,0 12,6 3 33,2 17,2 59,5 15,1 105,3 12,6 149,2 12,4 4 26,8 19,9 48,2 21,8 86,3 19,0 122,4 17,7 5 31,7 15,8 56,9 13,5 102,0 12,1 144,8 13,0 6 26,6 13,6 47,3 12,0 84,6 13,8 119,1 12,5 7 31,1 13,8 54,6 11,4 97,9 12,0 139,1 12,4 8 24,8 13,0 43,0 10,3 76,9 9,8 108,2 9,4 9 30,8 23,2 55,1 16,2 98,9 12,9 141,2 14,3 10 28,9 20,5 50,7 12,7 90,2 14,5 127,2 11,9 11 24,3 14,1 41,1 12,5 72,5 14,5 101,6 13,5 12 27,7 19,3 50,0 13,5 90,3 12,5 127,4 12,2 13 25,3 13,9 44,6 13,5 79,8 12,6 112,1 11,1 14 22,8 12,4 38,5 10,0 66,2 9,8 91,4 9,1 15 31,3 13,7 55,5 11,4 100,6 10,4 142,4 11,3 16 29,0 22,6 52,2 19,4 93,2 15,2 132,6 12,8 17 24,0 15,0 41,6 14,7 72,7 14,9 101,7 14,1 18 26,6 18,7 47,6 16,7 84,3 9,9 119,1 9,7 19 30,9 17,0 55,1 13,2 99,0 13,0 140,0 13,7 20 26,6 12,1 46,9 11,8 84,0 11,7 117,8 10,9 21 23,1 11,8 39,9 12,5 68,1 9,9 94,5 10,9 22 30,3 13,5 54,0 12,6 96,7 11,5 136,4 11,0 23 24,3 16,2 42,9 14,3 77,0 16,3 108,0 12,1 24 28,9 19,1 53,4 18,0 96,3 14,6 137,2 15,4 25 31,8 15,2 56,7 15,5 102,1 14,1 145,2 12,7 26 27,7 17,6 49,3 14,0 89,2 12,8 125,8 11,6 27 22,7 15,1 38,6 14,6 67,3 12,2 94,2 13,1 28 30,5 13,2 55,1 10,0 99,6 11,2 140,6 11,3 29 26,2 10,4 44,8 11,7 78,6 11,1 111,4 11,4 30 26,3 8,8 47,2 8,7 85,4 8,9 120,8 8,6 31 27,0 7,5 48,9 8,1 88,7 9,4 125,6 9,0 32 24,7 16,1 44,1 14,5 79,2 14,3 111,1 13,7 33 31,8 16,3 56,7 16,4 103,2 15,5 146,7 15,7 Id -Identificação da estação; ETo -Método de Penman-Monteith preconizado pela FAO-56; ETo5 -5 dias; ETo10 -10 dias; ETo20 -20 dias; ETo30 -30 dias acumulados Por meio da função de distribuição acumulada de Gumbel II foram gerados os valores de ETo para os níveis de probabilidade de 50, 70, 80, 90 e 95%, correspondendo ao tempo de retorno de 2, 3, 5, 10 e 20 anos, respectivamente (Figura 6 a 9).…”
Section: Resultsunclassified